2018
DOI: 10.1164/rccm.201703-0532oc
|View full text |Cite
|
Sign up to set email alerts
|

Activated Leukocyte Cell Adhesion Molecule Stimulates the T-Cell Response in Allergic Asthma

Abstract: ALCAM contributes to OVA-induced allergic asthma by stimulating T-cell activation and proliferation, suggesting it as a potential therapeutic target for allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…FACS analysis confirmed constitutive expression of CD6 in CD4 + OTII T cells and of ALCAM in BM-DCs (Figure 2F). Similarly to two recent reports (10, 11), we found that in vitro proliferation (Figures 2G,H) and IFN-γ production (Figure 2I) of OTII T cells were significantly reduced in co-cultures involving ALCAM −/− DCs. Moreover, treatment of co-cultures involving WT DCs with I/F8-Fc reduced T cell proliferation and IFN-γ production to similar levels as observed in co-cultures of T cells and ALCAM −/− DCs (Figures 2H,I).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…FACS analysis confirmed constitutive expression of CD6 in CD4 + OTII T cells and of ALCAM in BM-DCs (Figure 2F). Similarly to two recent reports (10, 11), we found that in vitro proliferation (Figures 2G,H) and IFN-γ production (Figure 2I) of OTII T cells were significantly reduced in co-cultures involving ALCAM −/− DCs. Moreover, treatment of co-cultures involving WT DCs with I/F8-Fc reduced T cell proliferation and IFN-γ production to similar levels as observed in co-cultures of T cells and ALCAM −/− DCs (Figures 2H,I).…”
Section: Resultssupporting
confidence: 91%
“…Moreover, ALCAM on DCs interacting with T cell-expressed CD6 was shown to provide T cell co-stimulation in vitro (9). In line with the latter findings, two recent studies reported that ALCAM-deficient (ALCAM −/− ) mice are partially protected from T cell-mediated inflammation in murine models of asthma (10) and food allergy (11). In ECs ALCAM was shown to mediate in vitro migration, tube formation and barrier function of blood vascular and lymphatic ECs (LECs) (2, 12, 13).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Prior studies demonstrated that ALCAM contributes to ovalbumin (OVA)-induced allergic asthma and food allergy by stimulating T-cell activation and proliferation 2829. Although ALCAM is associated with hypersensitivity and T cell activation in the initiation of immune responses, its function in AD has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%